Determinan Ketimpangan Indeks Pembangunan Manusia di Provinsi Jambi - Arniwita Arniwita; Deka Veronica; Ahmad Soleh (Universitas Batanghari, 2020)
The Human Development Index (HDI) is an index to measure human achievement and is one of the indicators used in looking at people's well-being in a region. The higher the HDI value in a region, the better the level of welfare in the region. So often HDI is considered to have been able to represent the welfare level of the population, because in the HDI includes elements that include economic and noneconomic variables. Non-economic variables are measured from the level of public education and the degree of public health. While economic variables are measured from income levels indicating people's purchasing power, the three are related to each other. However, if you look at the conditions in Jambi Province, there is an interesting phenomenon where the development of the government does not or lack a real impact on the improvement of the Human Development Index (HDI), so it is necessary to do this research. The purpose of this study is to analyze the inequality, influence and relationship of the variables of the human development index which includes Gross Regional Domestic Product (GRDP) per capita, the number of medical personnel, the number of basic health facilities, the number of poor people as well as the number of teachers in public elementary schools as dependent variables with the human development index (HDI) as dependent variables. The data analysis method used in this study is a qualitative and qualitative descriptive method of explanatory properties, using sekuder data in the period 2008-2017. The data analysis tool used in this study uses the usual Weighted Coefficient of Variation (CVw) method for the first problem, the subsequent regression of the data panel for the second problem and the person correlation for the third problem. The hypothesis test in this study shows that there is inequality in IPM-forming variables in Jambi Province, further influence and significant relationship between ipm-forming variable inequality and HDI in Jambi Province.